Kinetics of selenium absorption in ligated small intestinal loops of chicks - Guo-qing LIU; Shu-min ZHANG; Zhi-min AN; Yan-zhong FENG; Xue-yu DONG; Su-fen LI; Lin LU; Li-yang ZHANG; Run-lian WANG; Xu-gang LUO; Xiu-dong LIAO (Journal of Integrative Agriculture, 2020)
Selenium (Se) is an essential trace element that has a large number of biological functions for broilers. However, the absorption kinetics of Se from sodium selenite in the small intestine of broilers remains unclear. Therefore, two experiments were conducted with 28-d-old commercial male broilers to study the kinetics of Se absorption in ligated small intestinal segments. In experiment 1, the Se absorption in duodenal, jejunal, and ileal segments at different post-perfusion time points (0, 20, 40, 60, 80, 100 and 120 min) were compared. In experiment 2, a kinetic study of Se absorption was conducted with the duodenal, jejunal, and ileal loops perfused with solutions containing 0, 0.0375, 0.075, 0.15, 0.30, or 0.60 μg mL−1 of Se as sodium selenite, and Se contents in perfusates were determined at 100 min after perfusion. The results from experiment 1 showed that the Se absorption increased in an asymptotic response (P<0.0001) to post-perfusion time within 120 min in all the small intestinal segments, but increased linearly (P<0.0001) at less than 100 min after perfusion in duodenal and ileal segments, while more than 96.0% of the maximum Se absorption occurred at 100 min after perfusion in each small intestinal segment. In experiment 2, there was no difference (P>0.05) in the Se absorption rate among different ligated small intestinal segments perfused with solutions containing 0.0375–0.15 μg mL−1 of Se, however, the Se absorption rate was higher (P<0.05) in the jejunum than that in the duodenum perfused with solutions containing 0.30–0.60 μg mL−1 of Se. The kinetic curves of Se absorption demonstrated that the Se absorption was a saturated carrier-mediated process in the duodenum, and the maximum absorption rate was 1 271 pg min−1 cm−1; whereas the Se absorptions were a non-saturated diffusion process in the jejunum and ileum, and the diffusive constants were 2 107 and 1 777 cm2 min−1, respectively. The results from the present study indicate that the jejunum is the main Se absorption site, and the Se absorption is a saturated carrier-mediated process in the duodenum, but a non-saturated diffusion process in the jejunum and ileum of broilers.